Analysis of the Role of Human Resources Management in the Quality of Customer Service of PT PLN (Persero) Up3 Tanjung Karang - Ricky Novriyan Pradana; M. Oktaviannur (International Journal of Economics, Business and Innovation Research, 2024)
Customer service quality plays a crucial role in the success of an organization, especially in the energy supply sector such as PT PLN (Persero). This study aims to analyze the role of human resource management (HR) in improving the quality of customer service at PT PLN (Persero) Customer Service Implementation Unit (UP3) Tanjung Karang. The research method used is a survey with questionnaires distributed to employees and customers of PT PLN (Persero) UP3 Tanjung Karang. The results showed that HR management has a significant impact on customer service quality. Factors such as recruitment, training, and employee development have a positive relationship with customer satisfaction. In addition, internal communication, employee motivation, and reward systems also have an important role in improving employee performance and directly contribute to the quality of service provided to customers. This research contributes to the understanding of the close relationship between HR management and customer service quality in the context of the energy industry. The practical implications of this research can help PT PLN (Persero) UP3 Tanjung Karang in optimizing HR management strategies to increase customer satisfaction and maintain competitiveness in a competitive energy market. The conclusion of this research provides a foundation for similar companies to better understand the importance of the role of HR management in achieving strategic goals related to customer service quality.